Below‐ground biotic interactions moderated the postglacial range dynamics of trees. Issue 4 (17th May 2018) - Pither, Jason; Pickles, Brian J.; Simard, Suzanne W.; Ordonez, Alejandro; Williams, John W.
Summary: Tree range shifts during geohistorical global change events provide a useful real‐world model for how future changes in forest biomes may proceed. In North America, during the last deglaciation, the distributions of tree taxa varied significantly as regards the rate and direction of their responses for reasons that remain unclear. Local‐scale processes such as establishment, growth, and resilience to environmental stress ultimately influence range dynamics. Despite the fact that interactions between trees and soil biota are known to influence local‐scale processes profoundly, evidence linking below‐ground interactions to distribution dynamics remains scarce. We evaluated climate velocity and plant traits related to dispersal, environmental tolerance and below‐ground symbioses, as potential predictors of the geohistorical rates of expansion and contraction of the core distributions of tree genera between 16 and 7 kabp . The receptivity of host genera towards ectomycorrhizal fungi was strongly supported as a positive predictor of poleward rates of distribution expansion, and seed mass was supported as a negative predictor. Climate velocity gained support as a positive predictor of rates of distribution contraction, but not expansion. Our findings indicate that understanding how tree distributions, and thus forest ecosystems, respond to climate change requires the simultaneous consideration of traits, biotic interactions and abiotic forcing. Abstract : See also the Commentary on this article byZobel, 220: 947–949 .